The integrative role of uPAR in outside-in signalling in human oesophageal squamous cell carcinoma cells - Dahan, Yael-Leah (My University, 2012)
Early investigations of the urokinase type plasminogen activator (uPA) receptor (uPAR) and its ligand, uPA, were limited to their role in degradation of the extracellular matrix (ECM) and invasion. Emerging evidence revealed that uPAR and its relationship with uPA and/or transmembrane proteins, such as the integrins, affects cell-ECM adhesion events and proliferation. These events are tightly coordinated and essential for epithelial tissue development. However, unregulated expression of molecules involved in cell adhesion and proliferation plays a significant role in tumour development and metastasis. The overexpression of uPAR is linked to several cancer types, including human oesophageal squamous cell carcinoma (HOSCC). This study examines the contribution of uPAR, and its communication with extracellular components, to cell-ECM adhesion and/or proliferation of HOSCC cells. The confirmation of the uPAR and 1-integrin expression as well as uPA secretion in the HOSCC cells lines, established these lines as excellent models for further investigation. In all the HOSCC cell lines, uPAR associated with integrin-linked kinase, a scaffolding protein in cell-ECM adhesion events. Data presented in this investigation confirmed that the interaction of uPAR with uPA or 1-integrin contributed to adhesion of the HOSCC cell lines on collagen type I and vitronectin. It was clearly established that uPAR also played a part in the proliferation of all the HOSCC cell lines. The uPAR role in proliferation is influenced by: a) The absence or presence of collagen type I or vitronectin substrates; b) The activation of uPAR by endogenous uPA; c) The uPAR/1-integrin interaction; d) the presence of transforming growth factor  and epidermal growth factor. In the current study, it was successfully demonstrated that uPAR, and its relationship with the ECM and growth factors, contributes to adhesion and proliferation during the progression of HOSCC. This gives uPAR a considerable value as a therapeutic target for HOSCC.
Keywords: Esophagus - Cancer.; Cancer.; Cell differentiation.; Squamous cell carcinoma.